Theological Meaning of The Munggahan Ramadhan Ritual in Bandung, West Java - Didin Komarudin; Siti Rohmah (El Harakah, 2022)
Rituals are sacred religious teachings based on beliefs that will give birth to peace and blessings in the life of the believers. One of them is the Munggahan ritual which is still carried out by the people of Bandung, West Java. This study aimed to determine how the ritual process was carried out and to understand the theological meaning of the Munggahan ritual carried out by the people of Bandung. The design used in this research is descriptive method that systematically explains the facts in the field through the anthropological approach of religion. The data collection process employed observation and interview. The informants were the chairman and several members of the Bandung community. The result shows that the theological meaning of the Munggahan ritual in the month of Ramadan is a form of cleansing oneself from bad things during the past year as well as a form of expression of gratitude for what Allah has given. It also conveys the hope to be given the convenience, safety, health and to avoid bad deeds during worship during Ramadan.